Christian social activism and rule of law in Chinese societies - Yang, Fenggang; White, Chris (Studies in Christianity in China, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Contents -- Preface -- Chapter 1: A Historical Overview of Chinese Christian Activism: Institutional Change toward Democracy -- Christians in the Founding of the Republic of China -- Christians in the New Republic and the Campaign for Religious Freedom in the Constitution -- Christians in the Democratization of Taiwan -- Ongoing Christian Activism in Hong Kong -- Chinese Christian Activism in the PRC and Exile -- Conclusion -- Notes -- Bibliography -- Part I: Chinese Christian Activism in the Republic of China on Taiwan -- Notes -- Bibliography -- Chapter 2: Taiwan under Martial Law and Presbyterian Responses -- Introduction -- Martial Law and the Christian Condition -- Exile, Imprisonment, and Assassination -- Indigenous Growth and Development -- PCT as a Gateway -- A PCT Theology? A PCT Public Witness? -- Conclusions -- Author's NOTE -- Notes -- Bibliography -- Chapter 3: To Unite as One Body: The Presbyterians and Changing Identities in Taiwan -- Introduction -- Chinese or Taiwanese? -- The Church as the Promoter of a New Identity -- New and Independent Taiwan -- Recent Developments -- Conclusion -- Notes -- Bibliography -- Part II: Chinese Christian Activism in Hong Kong -- Notes -- Bibliography -- Chapter 4: Religious Discourse, Social Participation, and Identity Construction of Hong Kong Protestant Christians from 1970 to 1997: An Analysis of Three Oral Histories -- Introduction -- Christian Social Participation and Church-State Relations in Colonial Hong Kong from 1970 to 1997 -- Social Participation and Identity Construction of Hong Kong Christians in Colonial Hong Kong -- Kwok Nai Wang: Leader and Crystallizer -- Lau Chin Shek: Labor Activist and Legislator -- Chan Cho Wai Joseph: Apologist and Intellectual for Democratic Development -- Concluding Remarks -- Notes.